Advanced nurse practitioners composure behavior and patients' wellness outcome - Divinagracia, Carmelita C.
The advance concept leading to independent nursing practice is still in the developing and development process. Since the practice of nursing deals with life and involves person to person transactions, it is but imperative to explore new horizon that will bring about transformation in the practice of nursing. While cardiac patients who are confined in the Critical Care Unit are being cared for by nurses who are trained by the institution to become competent, the need to integrated biobehavioral interventions in their practice need to be developed to enhance their holistic caring to their patients.~~~~The study was conducted to determine the effects of "COMPOSURE BEHAVIOR' of the Advanced Nurse Practitioner on the Wellness Outcome. The study population consisted of adult cardiac patients admitted and confined at the Philippine Heart Center, Coronary Care Unit. Nursing participants were professional nurses working in the coronany care unit with at least two years of bedside experience and had undergone the post-graduate training program offered by the Nursing Service of the Philippine Heart Center. As caregivers, they had also attended the "COMPOSURE Behaviors" Training Programs as the prime treatment modality for the study and which ismthe doctoral theory.~~~~The Quasi-Experimental three-group Prettest-Posttest was utilized in the study. The results revealed...
Disertation (Doctor of Philosophy in Nursing) -- University of the Philippines Manila
Keywords: Nurse practitioners; Wellness